Class actions within the field of environmental law - Dannecker, Regula (Department of Public Law, 2023)
In recent decades an awareness of the need to protect and conserve the environment has spread world wide. Today, environmental law is an important issue of every government and legislature, as well as a concern of many, individuals and environmental groups. Technological and industrial development rule today's societies in growing dimensions. The increasing 'massification', significant for westernised countries, also involve mass accidents and widespread environmental damage or pollution. A single factory, or for instance an oil refinery, can cause toxic fumes polluting the air, and thus causing significant harm to people and the environment. Massification can produce dangerous living or working conditions which demand the mass to become the focal point of change. In general, environmental law has developed a distinct public law character, concerned to protect the environment as a public good. However, civil litigation has some impact on this branch of law as well, either for its direct enforcement or for the redress of environmental and personal damage. With the rise of environmentally concerned individuals as well as associations, and with the increase of mass disasters or man-made hazards adequate remedies have to be found. Out of such incidents, affecting many people either directly or indirectly, new and complex legal situations emerge. Thus, class actions and actions in the public interest have become an important issue in many countries. This paper shall discuss the development of such class actions and the problems accompanying it, focusing in particular on the environmental law field. It will be demonstrated how this phenomenon, particularly strong in the United States, has been approached in the legal realm of different countries, one amongst them the Indian ·case of 'social action litigation'. Eventually, the situation in South Africa, especially in the light of the new Constitution and the new class action device, shall be discussed.